2022
DOI: 10.1039/d2nr01878k
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandex vivonano-enabled immunomodulation by the protein corona

Abstract: New technologies with the capacity to tune immune system activity are highly desired in clinical practice and disease management. Here we demonstrate that nanoparticles with a protein corona enriched by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…To develop optimized gene delivery systems, current investigations have focused on exploiting protein coatings on lipid-based gene delivery systems (GDSs) as a promising strategy. The design of precoated GDSs capitalizes on the targeting ability of plasma proteins obtained directly from the biological source. This protein coating acts as a functionalization acquired by LNPs upon exposure to the biological milieu .…”
Section: Resultsmentioning
confidence: 99%
“…To develop optimized gene delivery systems, current investigations have focused on exploiting protein coatings on lipid-based gene delivery systems (GDSs) as a promising strategy. The design of precoated GDSs capitalizes on the targeting ability of plasma proteins obtained directly from the biological source. This protein coating acts as a functionalization acquired by LNPs upon exposure to the biological milieu .…”
Section: Resultsmentioning
confidence: 99%
“…This protein corona significantly affects not only the NPs’ fate (pharmacokinetics, biodistribution, and target recognition), but also their effectiveness as therapeutic biocarriers and/or immunomodulators [ 154 , 155 , 156 ]. Interestingly, recent works have now opened the possibility to engineer the “protein corona” to modulate NP interaction with the immune system [ 157 , 158 ]. If this strategy could be used to improve NPs’ potential as immunomodulators deserves further investigation.…”
Section: Nanomedicine-based Strategies For Immunomodulationmentioning
confidence: 99%
“…75 The protein corona regulates the interaction with immune system cells in vitro and ex vivo. 76 These findings prompted us to create biomimetic lipoplexes with an artificial opsonin-deficient protein corona that minimizes the uptake by immune cells in vivo. 16 We have also demonstrated that the protein corona of lipoplexes locks onto receptors of cancer cells, promoting internalization by a receptor-mediated mechanism.…”
Section: ■ Future Research Directionsmentioning
confidence: 99%
“…In previous works, we have shown that the protein corona acquired by lipid vesicles has a composition that is simultaneously regulated by the electrical charge and by the affinity of lipids for individual proteins or specific classes of plasma proteins . The protein corona regulates the interaction with immune system cells in vitro and ex vivo …”
Section: Future Research Directionsmentioning
confidence: 99%